Studying phenotypic variation and DNA methylation across development, ecology and evolution in the clonal marbled crayfish: a paradigm for investigating epigenotype-phenotype relationships in macro-invertebrates - Vogt, Günter (The Science of nature, 2022)
Animals can produce different phenotypes from the same genome during development, environmental adaptation and evolution, which is mediated by epigenetic mechanisms including DNA methylation. The obligatory parthenogenetic marbled crayfish, Procambarus virginalis, whose genome and methylome are fully established, proved very suitable to study this issue in detail. Comparison between developmental stages and DNA methylation revealed low expression of Dnmt methylation and Tet demethylation enzymes from the spawned oocyte to the 256 cell embryo and considerably increased expression thereafter. The global 5-methylcytosine level was 2.78% at mid-embryonic development and decreased slightly to 2.41% in 2-year-old adults. Genetically identical clutch-mates raised in the same uniform laboratory setting showed broad variation in morphological, behavioural and life history traits and differences in DNA methylation. The invasion of diverse habitats in tropical to cold-temperate biomes in the last 20 years by the marbled crayfish was associated with the expression of significantly different phenotypic traits and DNA methylation patterns, despite extremely low genetic variation on the whole genome scale, suggesting the establishment of epigenetic ecotypes. The evolution of marbled crayfish from its parent species Procambarus fallax by autotriploidy a few decades ago was accompanied by a significant increase in body size, fertility and life span, a 20% reduction of global DNA methylation and alteration of methylation in hundreds of genes, suggesting that epigenetic mechanisms were involved in speciation and fitness enhancement. The combined analysis of phenotypic traits and DNA methylation across multiple biological contexts in the laboratory and field in marbled crayfish may serve as a blueprint for uncovering the role of epigenetic mechanisms in shaping of phenotypes in macro-invertebrates.
Gesehen am 07.09.2022